Survival Strategies of Mangrove (Ceriops tagal (perr.) C. B. Rob) and the Inspired Corrosion Inhibitor - Cui, Miaomiao; Wang, Zuankai; Wang, Bin (Frontiers in Materials, 2022)
Corrosion is ubiquitous, inevitable, and very common in our daily lives; it has been one of the most significant challenges and needs to be addressed by some novel approaches for the development of modern society. Corrosion-resisting strategies found in nature have been promising for the existence of many halophytes surviving in marine tidal zones facing high salinity and humidity. Among the halophytes, mangrove has developed a lot of functions to deal with such extreme conditions that could provide novel inspirations for the fabrication of engineering materials, especially for the material resisting corrosion. In this paper, we first investigated two survival strategies of mangroves, namely functional salt-secreting and mangrove tannin composite. Salt-secreting realized by mangrove salt glands could make mangrove excrete excessive salt and avoid harmful effects. On the other hand, mangrove tannin existing in large quantities in mangrove bark could help mangrove survive some marine bacteria. Inspired by the functional mangrove tannin, we developed a corrosion inhibitor to protect Q235 carbon steel in acid 3.5 wt% NaCl solution. Furthermore, we found that the mangrove-inspired corrosion inhibitor could be adsorbed at the metal–solution interface, functioning as a cathodic inhibitor with 60.51% anti-corrosion efficiency.